Effects of Pharmaceutical Mestranol on Estrogen Receptor β mRNA Expression Levels and Morphometry in the Anal Fins of Adult Thai Riceﬁsh (Oryzias minutillus) - Ngamniyom, Arin; Silprasit, Kun; Panyarachun, Busaba (Agriculture and Natural Resources, 2012)
This study aimed to examine the estrogen receptor (ER) β mRNA expression levels and morphometry of the anal ﬁ n of adult Thai riceﬁ sh (Oryzias minutillus) after treatment with pharmaceutical mestranol. Time- and concentration-related courses of mestranol on ERβ expression were investigated in anal ﬁ ns by semi-quantitative reverse transcription polymerase chain reaction. In the time course experiments, ERβ expression levels in male anal ﬁ ns were increased at 30 d after treatment with 10 μg.mL-1 of mestranol. ERβ levels in female anal ﬁ ns were highly expressed at 21, 30 and 60 d after mestranol treatment. In the concentration-response experiment, ERβ levels were increased in males after treatment with 10 μg.mL-1 of mestranol for 21 d and in females treated with 0.1, 1, or 10 μg.mL-1 mestranol for 21 d. Morphometrical analysis showed that the proportion of anal ﬁ n length to standard length was low in males after 10 μg.mL-1 mestranol treatments for 30 and 60 d. In contrast, there was no morphometrical difference in females after exposure to mestranol in any of the treatments analyzed. The results suggested that mestranol regulates the sex-dependent morphology of anal ﬁ n in development at least in part by mediating ERβ expression and may lead to the disruption of endocrine activities in ﬁsh.